The legal person and its other: a comparative view on drawing and effacing boundaries in various cultural contexts - Suntrup, Jan Christoph; Justus Liebig University Giessen (My University, 2017)
Focusing on the project of de-humanizing law calls for a discussion of the concept of the legal person for two reasons. Firstly, legal processes of personification have at times gone beyond the anthropocentric bias in legal thinking; secondly, the definition of personhood has often brought about de-humanizing results. By scrutinizing various culturally and historically dependent drawings of the boundaries of personification, it can be shown that the presumed equivalence between legal persons and humans does not hold. This can be illustrated through an analysis of legal personification of animals as well as some recent legal attempts to attribute personality to nature. In contrast to these inclusionary processes of personification, there have always also been efforts to deny certain human beings the status of legal persons. Despite becoming more inclusive historically, modern law does not eschew with creating abnormal non-persons (beasts, monsters, dangerous beings, etc.) in order to underline the construction of individual/rational attribution and accountability. Defining legal personhood not only implies a differentiation between persons and non-persons, but, especially in the Western world, between persons and things. Whereas bio-political issues have somewhat challenged this division, there are examples showing that in some contexts this division was never made clearly in the first place. Finally, the analysis of problems that current international copyright law faces when dealing with questions of traditional knowledge and cultural heritage reveals the occidental bias concerning the conception of personhood, namely its link to an individualized image of the ingenious author.
Keywords: cultural comparison; human dignity; human-animal divide; indigenous culture; legal history; ddc:300